ANALISA PENGARUH BENTUK LEKUKAN PIPA KAPILER DAN DIAMETER BERBEDA TERHADAP SUHU EVAPORATOR PADA REFRIGERATOR JENIS DISPENSER - Martini, Ninik; Sabtadi, Catur Hari (MEKANIKA: Jurnal Teknik Mesin, 2015)
Dispenser is an electronic device to drain the water of gallons of water into the cup or glass that can automatically heats and cools water that is ready to drink. Also called water cooler dispenser (water cooler), butalong with the development of technology and the increasing complexity of human needs, the dispenser is not onlyused to cool water, dispenser also can heat the water using a heater. On the dispenser there is a straight capillarytube where the capillary tube is one of the important components in the engine cooler (dispenser) and had aconsiderable influence on the size of the resulting temperature on the evaporator. This study used a variation incapillary tube spiral shape and forms a straight capillary tube with a diameter of 0.026 cm pipe; 0.028 cm; 0.031cm and a fixed length of 100 cm.The results were obtained in the form of a capillary tube straight with the lowest temperature evaporator isgenerated at 0,026 cm diameter pipe, with a temperature of - 10 0C and the resulting high temperature evaporatorin the form of straight capillary tube with a pipe diameter of 0.031 cm, with a temperature of 0 C. And achievementcoefficient (COP), which is the highest form of straight capillary tube with a diameter of 0.026 cm, with a value ofCOP = 13.896. and value is the lowest COP spiral shape of the capillary tube with a diameter of 0.028 cm, with avalue of COP = 10.761.Keyword : Capilary Tube ,Coefficient Of Performance (COP), Temperature of Evaporatio